Uji Aktivitas Daya Hambat Antimikroba Produk Antiseptik Hand Sanitizer dan Sabun Cair terhadap Bakteri Staphylococcus aureus - Purbosari, Ira (Universitas PGRI Adi Buana, Surabaya, 2021)
Washing hands is the first step to avoid various germs that cause infectious diseases, but this step is often ignored or overlooked. The use of hand sanitizer antiseptics and liquid soap is recommended early to avoid various types of germs that cause infectious diseases. Liquid soap can make viruses and bacteria unable to infect and reproduce. Because fat or lipids are damaged by detergents. Apart from antiseptic soap, hand sanitizers can disinfect and clean hands without soap. Hand sanitizers contain antibacterial ingredients such as triclosan or other antimicrobial agents which can inhibit the growth of bacteria on the hands such as Staphylococcus aureus. The purpose of this study was to determine the comparison of the effectiveness test of washing hands using antiseptic soap, running water, and hand sanitizer. In this study, the method used was the disc diffusion technique and the zone of inhibition was determined. This study uses 5 kinds of hand sanitizers that already have a distribution permit and negative control in the form of oil carriers. And the antimicrobial inhibition test was carried out with Staphylococcus aureus bacteria. Of the five hand sanitizer samples, there is an inhibition zone, namely in the sample HS code 1 (70 percent alcohol and castor oil) and HS 5 (70 percent alcohol), where the diameter of the inhibition zone is 1.8 mm and 4.3 mm. This shows that the response to growth inhibition of Staphylococcus aureus bacteria is very weak. Therefore, it can be concluded that the antibacterial activity of locally produced liquid soap and hand sanitizer is very weak in inhibiting Staphylococcus aureus bacteria.